Ecological Awareness in Buying and Selling: Fiqh al-Bi’ah Analysis on Plastic Bag Use at Tanjung Bajure Market, Indonesia - Elvi Nilda; Rifqi Nurdiansyah; Doli Witro; Mohammad Hidayaturrahman; Rahmad Setyawan; Raid Alghani (Faculty of Sharia (Islamic Law) at Fatmawati Sukarno State Islamic University Bengkulu, 2025)
This article aims to analyse the level of ecological awareness of traders and buyers at Tanjung Bajure Market in Sungai Penuh in the use of plastic bags and review how the government’s role in setting regulations through the perspective of Islamic law. This article is a juridical-empirical legal research with a socio-legal approach that uses qualitative methods and purposive sampling techniques. Data were obtained through observation at Tanjung Bajure Market, interviews with market players, and documentation, then the data were analysed through qualitative data analysis techniques namely data condensation, data presentation, and conclusion drawing. The results of the study found that the level of ecological awareness of the Tanjung Bajure Market in Sungai Penuh is still low, indicated by the dominance of the use of disposable plastic bags, although a small proportion of buyers have brought their own shopping bags. Government policies related to restrictions on the use of plastic bags have been regulated through various regulations, but their implementation has not been effective in traditional markets. In the perspective of Islamic law, consumptive behaviour towards plastic is considered contrary to the principles of maqashid sharia, especially in preserving the environment (hifz al-bi’ah). This research has contributed to the development of contemporary fiqh and Islamic economics, by recommending the formulation of fatwa provisions on the use of plastic bags based on Islamic ethics and ecological values. The implementation of the fatwa is certainly not immediately accepted by the actors, if it is not accompanied by ecological awareness of the actors. The findings of this study confirm that the importance of integration between the implementation of government regulations and religious ethics in order to form a sustainable and environmentally sound market ecosystem in accordance with Islamic values and ethics